Novel approach to constructing laser ionization elemental time-of-flight mass spectrometer. Issue 1 (February 2018) - Sysoev, Alexander A; Karpov, Alexander V; Milyaeva, Violetta V; Sysoev, Alexey A
The main advantages of laser sampling are associated with following features: sample preparations as well as consumables are not needed, low risk of sample contamination, good spatial resolution. In mass spectrometry, high laser irradiance can be used for both ablation and ionization processes. The method is especially profitable in time-of-flight mass spectrometry. A new principle of constructing laser ionization time-of-flight mass spectrometer based on wedge-shaped ion mirrors and the absence of electrostatic ion acceleration before mass analysis is discussed. Among advantages of the analyzer there are ability to provide temporal focusing of ions in a wide energy range (±20%), compactness of the analyzer, and minimization of the requirements for power supplies. The approach is expected to be profitable for standardless elemental analysis of solid samples, which should be possible at laser irradiation power density more than 3 × 10 9  W/cm 2 that ensures complete ionization of all elements in a laser plasma. The analytical signal of each element is formed as the sum of the signals for all charge states and the energy scan of the mass spectra is provided.